Sex differences in cardiovascular risk factors for dementi - Kim, Mi Young; Kim, Kyeongjin; Hong, Chang Hyung; Lee, Sang Yoon; Jung, Yi Sook (Biomolecules and Therapeutics, 2018)
Dementia, characterized by a progressive cognitive decline and a cumulative inability to behave independently, is highly associated with other diseases. Various cardiovascular disorders, such as coronary artery disease and atrial fibrillation, are well-known risk factors for dementia. Currently, increasing evidence suggests that sex factors may play an important role in the pathogenesis of diseases, including cardiovascular disease and dementia. Recent studies show that nearly two-thirds of patients diagnosed with Alzheimer’s disease are women; however, the incidence difference between men and women remains vague. Therefore, studies are needed to investigate sex-specific differences, which can help understand the pathophysiology of dementia and identify potential therapeutic targets for both sexes. In the present review, we summarize sex differences in the prevalence and incidence of dementia by subtypes. This review also describes sex differences in the risk factors of dementia and examines the impact of risk factors on the incidence of dementia in both sexes.
Keywords: Cardiovascular risk factors; Dementia incidence; Dementia prevalence; Sex difference